Unlocking Opportunities: Learning Beyond Experience Trough Benchmarking from UMT to UAD - Nargis, Nargis -; Cintya, Desmi Ayu; Melyana, Mita -; Lintang, Yunita -; Cintya, Novi -; Putri, Riana Andriana (Universitas Muhammadiyah Tangerang, 2024)
AbstractBenchmarking is an activity in education that is carried out to compare various aspects of two or more institutions within an educational institution, be it a school, university or other educational institution. The activity was carried out by a group of students from Muhammadiyah University, Tangerang, and Ahmad Dahlan University, Yogyakarta. In this comparative study activity, students took part in a workshop with the theme